Emerging mAbs for the treatment of esophagogastric cancer. (March 2015) - Ku, Geoffrey Y; Ilson, David H
<x xml:space="preserve">Abstract</x> Introduction: Owing to the poor prognosis for patients with esophagogastric cancers, increasing attention has focused on targeted agents. Areas covered: Targets include EGFR, VEGF, Her2 and MET. We briefly discuss preclinical data and the rationale for targeting these pathways and summarize the results of clinical trials of mAbs against these targets. Expert opinion: Trastuzumab, an anti-Her2 antibody, was approved by the US FDA in 2010 as first-line therapy in combination with chemotherapy for Her2-positive disease. More recently, two Phase III second-line trials of ramucirumab, an anti-VEGF receptor 2 antibody, as monotherapy or combined with chemotherapy showed improved survival. A prior Phase III evaluation of bevacizumab, an anti-VEGF antibody, with first-line chemotherapy was negative. While anti-EGFR therapy has been extensively investigated, completed Phase III trials suggest that this is not a promising target. Finally, MET inhibition appears to have significant clinical potential, and Phase III testing of an anti-MET pathway mAb is under way.